Characterization and analysis of the tensile and acoustic emission parameter distributions of single wool fibers. Issue 21 (November 2020) - Lu, Di; Yu, Weidong
Acoustic emission (AE) parameters of damaged material have discrete characteristics that are universally known. Such characteristics restrict wider use of AE analysis in materials such as textiles. In the present work, the best-fitted distribution models of AE signal energy are analyzed: amplitude, duration, tensile breaking strength, elongation, and specific work of wool fibers. The parameters of Weibull, normal, and log-normal distribution models are obtained by regression analysis. The chi-square, Kolmogorov–Smirnov, and maximum likelihood criterions are used to discriminate against the above models. The results show that the Weibull distribution is the best-fitted model for amplitude and elongation of wool. The best-fitted model for energy, strength, and specific work is the log-normal distribution. The differences between the cumulative distributions of the AE and tensile parameters are compared. It can be seen that strength also has a high correlation coefficient and a similarly cumulative distribution with energy and amplitude. Compared to amplitude, the relationship between energy and strength is supposed to be stronger.